Stunting berhubungan dengan perkembangan motorik anak di Kecamatan Sedayu, Bantul, Yogyakarta - Maria Goreti Pantaleon; Hamam Hadi; Indria Laksmi Gamayanti (Alma Ata University Press, 2015)
ABSTRACTBackground: Stunting (short body length) is a body condition that is very short until surpass deficit at 2 SD under median of body length or body height of the population that be an international reference. The cause of stunting is food consumption that is not balanced and infectious disease. Many studies showed the correlation between stunting and poor motoric and mental development in early childhood, and poor cognitive performance and school performance in later childhood. The national prevalence of stunting in 2013 was 37.2%, it increased compared to 2010 (35.6%) and 2007 (36.8%).Objectives: To know the correlation between stunting incidence and the development of 6-23 months old children in Sedayu Subdistrict, Bantul, Yogyakarta.Methods: This was observational study with cross sectional design. The sample size was 100 children, whose aged 6-23 months old. They consisted of 50 stunting children and 50 non-stunting children who were selected by consecutive sampling methods. Data were collected by using structured questionnaire and assisted by psychologist to measure the development of the children. Stunting in 6-23 months old children was measured by indicator of body length for age (WHO 2005) and the measurement of development used method of Bayley Scales of Infant Development III. Data were analyzed using chi-square test and logistic regression test by 95% confidence interval.Results: Statistically, there was signifi cant correlation between stunting and motoric development of the toddler (p=0.002), but there was no significant correlation between stunting and the development of cognitive, language, socio- emotional, and adaptive of the toddler. The result of multivariate showed thatstunting and sex statistically had correlation to the motoric development (p<0.05).Conclusions: Stunting associated with children motoric development in Sedayu Subdistrict, Bantul,YogyakartaKEYWORDS: children development, stuntingABSTRAKLatar belakang: Stunting (tubuh pendek) adalah keadaan tubuh yang sangat pendek hingga melampaui defisit 2 SD di bawah median panjang atau tinggi badan populasi yang menjadi referensi internasional. Penyebab stunting adalah konsumsi makanan yang tidak seimbang dan penyakit infeksi. Sejumlahpenelitian memperlihatkan keterkaitan antara stunting dengan perkembangan motorik dan mental yang buruk dalam usia kanak-kanak dini, serta prestasi kognitif dan prestasi sekolah yang buruk dalam usia kanak-kanak lanjut. Prevalensi stunting secara nasional tahun 2013 adalah 37,2%, yang berarti terjadi peningkatan dibandingkan tahun 2010 (35,6%) dan 2007 (36,8%).Tujuan: Untuk mengetahui hubungan antara kejadian stunting dengan perkembangan anak usia 6-23 bulan di Kecamatan Sedayu, Bantul, Yogyakarta.Metode: Penelitian ini merupakan penelitian observasional dengan rancangan cross sectional. Sampel penelitian sebanyak 100 anak yang berusia 6-23 bulan, terdiri dari 50 baduta stunting dan 50 baduta tidak stunting, dan dipilih dengan metode consecutive sampling. Pengambilan data menggunakan kuesioner terstruktur dan dibantu oleh tenaga psikolog dalam pengukuran perkembangan anak. Stunting pada anak usia 6-23 bulan diukur menggunakan indikator panjang badan menurut umur dan pengukuran perkembangan anak menggunakan metode Bayley Scales of Infant Development III. Analisis data menggunakan uji chi-square dan regresi logistik dengan 95% confi dent interval.Hasil: Secara statistik, ada hubungan signifikan antara stunting dengan perkembangan motorik baduta (p=0,002), namun tidak terdapat hubungan signifikan antara stunting dengan perkembangan kognitif, bahasa, sosioemosional, dan perkembangan adaptif baduta. Hasil uji multivariat menunjukkan bahwa stunting dan jenis kelamin secara statistik berkaitan dengan perkembangan motorik (p<0,05).Kesimpulan: Ada hubungan signifikan antara stunting dengan perkembangan motorik baduta diKecamatan Sedayu, Bantul, Yogyakarta.KATA KUNCI: perkembangan anak, stunting